Influence of Vermicompost and Biofertilizers on Yield and Economic Feasibility of Dragon Fruit - Pratap, Ravi; Tripathi, V. K.; Trivedi, A. K. (International Journal of Economic Plants, 2024)
An experiment was carried out in the Garden, Department of Fruit Science, C. S. Azad University of Agriculture and Technology, Kanpur (U.P.) during March to October 2022 and 2023 to evaluate the influence of vermicompost and biofertilizers on yield and economic feasibility of newly planted Dragon Fruit (Hylocereus costarecencis) in Kanpur region using eleven treatments viz., T1-Control; T2-Vermicompost (0.5 kg plant-1); T3-Azotobacter (50 g plant-1); T4-Azospirillium (50 g plant-1); T5-PSB (50 g plant-1); T6 -Vermicompost (0.5 kg plant-1) and Azotobacter (50 g plant-1); T7-Vermicompost (0.5 kg plant-1) and Azospirillium (50 g plant-1); T8-Vermicompost (0.5 kg plant-1) and PSB (50 g plant-1); T9-Vermicompost (0.5 kg plant-1), Azotobacter (50 g plant-1) and Azospirillium (50 g plant-1); T10-Vermicompost (0.5 kg plant-1), Azotobacter (50 g plant-1) and PSB (50 g plant-1) and T11-Vermicompost (0.5 kg plant-1), Azospirillium (50 g plant-1) and PSB (50 g plant-1) in RBD with three replications. Data obtained during experimentation revealed that from the second year of planting, the yield and economics were significantly influenced by vermicompost and biofertilizer application. The maximum number of fruits per pillar (12.64), estimated yield (6.50 t ha-1), cost of cultivation (` 131645.60 ha-1), gross return (` 520000.00 ha-1), net return (` 388354.40 ha-1) and benefit: cost ratio (3.95) were found with vermicompost (0.5 kg plant-1), Azospirillium (50 g plant-1) and PSB (50 g plant-1) in the second year of planting which may increase in subsequent years due to increase the number of fruits and yield plant-1. Dragon fruit has high potential in northern India, remaining remunerative from the second year after planting and up to twenty years.